A rare case of left ventricular lead stabilization utilizing a coronary stent placement during CRT-D implantation - Agarwal, Deepak; Makhija, Aman; Mohanty, Arun; Mantri, Raja Ram (The European Research Journal, 2019)
During cardiac resynchronization therapy implantation, left ventricular lead placement involves transvenous placement of leads via the coronary sinus and into a tributary branch. At present, the most widely used method for left ventricular (LV) lead placement involves a transvenous LV lead placement via the coronary sinus into a tributary branch. Lead dislodgement is a common cause for reoperation. We describe a case where a coronary stent was placed to stabilize the lead against the vessel wall.